2019
DOI: 10.1007/s11625-019-00672-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital co-construction of relational values: understanding the role of social media for sustainability

Abstract: There is a deeply relational aspect to the systems people employ for sorting through and prioritizing plural values assigned to social-ecological interactions. Spurred by interpersonal relationships and adhesion to societal core values, such as justice and reciprocity, relational values go beyond instrumental and intrinsic approaches to understanding human behaviour vis-à-vis the environment. Currently, this relational dimension of values is entering the spotlight of the Cultural Ecosystem Services (CES) liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 69 publications
(142 reference statements)
1
61
0
Order By: Relevance
“…We find tweets both identified multiple CES per tweet and the presence of multiple CES in zones of Prospect Park. This finding supports a recent review that found social media data can reveal CES values' plural and relational dimensions [57]. Tweets are public messages meant to be shared, with reception of the message read, interpreted, and commented upon by more people than a single interviewer, which may explain some differences between tweets and interviews in the type and proportions of CES elicited.…”
Section: Discussionsupporting
confidence: 88%
“…We find tweets both identified multiple CES per tweet and the presence of multiple CES in zones of Prospect Park. This finding supports a recent review that found social media data can reveal CES values' plural and relational dimensions [57]. Tweets are public messages meant to be shared, with reception of the message read, interpreted, and commented upon by more people than a single interviewer, which may explain some differences between tweets and interviews in the type and proportions of CES elicited.…”
Section: Discussionsupporting
confidence: 88%
“…He proposes multiple principles of normative valuation formation; for example, the importance of social units as the scale of analysis, procedural justice in the deliberation of shared social values, instrumental outcomes being informed by deliberative valuation, and new dialectical approaches to decision-making. Calcagni et al (2019) in contrast consider non-monetary shared social values, exploring how multimedia content coconstructed by the users would expose the relational nature of social values assigned to cultural ecosystem services. These authors conduct a systematic review of studies of cultural ecosystem services using social media and find that recreation values were most frequently quantified, in addition to landscape aesthetics and cultural identity.…”
Section: How Do We Integrate or Establish Shared Social Values?mentioning
confidence: 99%
“…These observations suggest that variability in correlations between social media and on-site visitor counts seen here and in previous studies 8,12,20 is derived from local factors influencing visitors' day-to-day decisions about whether and how to share a destination on social media. Choices about whether to post to social media are likely influenced by the characteristics of the local site -perhaps its topography, amenities, predominant activity, or unique natural features -and the ways that people relate to these features 33 . The characteristics of the visitors and the relative contributions of the natural versus the social experience in the motivation for the trip may play a role.…”
Section: Discussionmentioning
confidence: 99%